Zoledronate for prevention of bone erosion in tophaceous gout: a randomised, double-blind, placebo-controlled trial. Issue 6 (17th January 2014) - Dalbeth, Nicola; Aati, Opetaia; Gamble, Gregory D; Horne, Anne; House, Meaghan E; Roger, Mark; Doyle, Anthony J; Chhana, Ashika; McQueen, Fiona M; Reid, Ian R
Abstract : Objectives: The osteoclast has been implicated in development of bone erosion in gout. The aim of this study was to determine whether zoledronate, a potent antiosteoclast drug, influences bone erosion in people with tophaceous gout. Methods: This was a 2-year, randomised, double-blind, placebo-controlled trial of 100 people with tophaceous gout. Participants were randomised to annual administration of 5 mg intravenous zoledronate or placebo. The primary endpoint was change in the foot CT bone erosion score from baseline. Secondary endpoint was change in plain radiographic damage scores. Other endpoints were change in bone mineral density (BMD), bone turnover markers and the OMERACT-endorsed core domains for chronic gout studies. Results: There was no change in CT erosion scores over 2 years, and no difference between the two treatment groups at Year 1 or 2 (p(treat) =0.10, p(time) =0.47, p(treat*time) =0.23). Similarly, there was no change in plain radiographic scores over 2 years, and no difference between the two groups at Year 1 or 2. By contrast, zoledronate increased spine, neck of femur, total hip and total body BMD. Zoledronate therapy also reduced the bone turnover markers P1NP and β-CTX compared with placebo. There was no difference between treatment groups in OMERACT-endorsed core domains. Conclusions: Despite improvements in BMD and suppression of bone turnover markers, antiosteoclast therapy with zoledronate did not influence bone erosion in people with tophaceous gout. These findings suggest a disconnect between responses in the healthy skeleton and at sites of focal bone erosion in tophaceous gout.